2022
DOI: 10.3390/pharmaceutics14091864
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, In Vitro Characterization, and Cytotoxicity Evaluation of Polymeric pH-Responsive Hydrogels for Controlled Drug Release

Abstract: The aim of the current investigation was based on the development of pH-responsive hydrogels of chondroitin sulfate, carbopol, and polyvinyl alcohol polymerized with acrylic acid in the presence of ammonium persulfate and ethylene glycol dimethylacrylate for controlled drug delivery. A free radical polymerization technique was used for the preparation of these pH-responsive hydrogels. The gel fraction of the prepared hydrogels was increased with the increase in the chondroitin sulfate, carbopol, polyvinyl alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Several studies demonstrated that higher swelling ability leads to increased drug loading and drug release rates. For example, Suhail et al [ 45 ] reported a decreased drug loading capacity of chondroitin sulfate-based hydrogels that presented lower swelling when compared to the ones with higher swelling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that higher swelling ability leads to increased drug loading and drug release rates. For example, Suhail et al [ 45 ] reported a decreased drug loading capacity of chondroitin sulfate-based hydrogels that presented lower swelling when compared to the ones with higher swelling.…”
Section: Resultsmentioning
confidence: 99%
“…However, a similar release percentage (>90%) was obtained after 130 min of the experiment. This difference might be attributed to the higher swelling ability of CGC-based hydrogels, at pH 7, which allows an increase in the drug release rate from the structure [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The porosity of the HMs has an important role in several physicochemical properties of the structures, mainly those related to swelling behavior and drug loading ability [ 37 , 38 ]. As predicted by the SEM observations, the hydrogels’ porosity decreased as the polymer content increased.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, those structures presented a Tdeg of 271–272 °C, which is slightly higher than the value displayed by FucoPol (266 °C). These results suggest that the HMs had higher thermal stability, likely given by the crosslinking and coordinate interactions between Fe 3+ and FucoPol [ 38 ]. Enhanced thermal stability was also reported for Fe 3+ -konjac glucomannan hydrogels, which presented a higher Tdeg (275 °C) than those of the other konjac glucomannan-based samples (235–265 °C) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, repulsive interaction between nexus was significant. It means formulated hydrogel has good pH sensitivity, strength and swelling degree (Suhail et al, 2022).…”
Section: Hydrogelsmentioning
confidence: 99%